Establishing anchor-based minimally important differences for the EORTC QLQ-C30 in glioma patients. Issue 8 (18th February 2021) - Dirven, Linda; Musoro, Jammbe Z; Coens, Corneel; Reijneveld, Jaap C; Taphoorn, Martin J B; Boele, Florien W; Groenvold, Mogens; van den Bent, Martin J; Stupp, Roger; Velikova, Galina; Cocks, Kim; Sprangers, Mirjam A G; et al.
Abstract: Background: Minimally important differences (MIDs) allow interpretation of the clinical relevance of health-related quality of life (HRQOL) results. This study aimed to estimate MIDs for all European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30) scales for interpreting group-level results in brain tumor patients. Methods: Clinical and HRQOL data from three glioma trials were used. Clinical anchors were selected for each EORTC QLQ-C30 scale, based on correlation (>0.30) and clinical plausibility of association. Changes in both HRQOL and the anchors were calculated, and for each scale and time period, patients were categorized into one of the three clinical change groups: deteriorated by one anchor category, no change, or improved by one anchor category. Mean change method and linear regression were applied to estimate MIDs for interpreting within-group change and between-group differences in change over time, respectively. Distribution-based methods were applied to generate supportive evidence. Results: A total of 1687 patients were enrolled in the three trials. The retained anchors were performance status and eight Common Terminology Criteria for Adverse Events (CTCAE) scales. MIDs for interpreting within-group change ranged from 4 to 12 points for improvement and −4 to −14 points for deterioration. MIDs for between-group difference in change ranged from 4 to 9 for improvement and −4 to −16 for deterioration. Most anchor-based MIDs were closest to the 0.3 SD distribution-based estimates (range: 3-10). Conclusions: MIDs for the EORTC QLQ-C30 scales generally ranged between 4 and 11 points for both within-group mean change and between-group mean difference in change. These results can be used to interpret QLQ-C30 results from glioma trials.